Prediction of the Catalyst Activity in the Process of Vacuum Gas Oil Hydrocracking Using a Mathematical Model; Petroleum and Coal; Vol. 66, iss. 4 - Belinskaya N. S. Natalia Sergeevna (2024, 2024)
Title screen.